1003 ch 10 day 3

297 views

Published on

Published in: Education, Technology
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
297
On SlideShare
0
From Embeds
0
Number of Embeds
2
Actions
Shares
0
Downloads
0
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • \n
  • 1003 ch 10 day 3

    1. 1. 10.2 The EllipsePsalm 63:5 "My soul will be satisfied as with fat and richfood, and my mouth will praise you with joyful lips,"
    2. 2. Another way to define the ellipse is this:An Ellipse is the set ofpoints in the plane thesum of whose distancesfrom two fixed points(the Foci), is a constant. use K on keyboard to Pause/Play
    3. 3. Another way to define the ellipse is this:An Ellipse is the set ofpoints in the plane thesum of whose distancesfrom two fixed points(the Foci), is a constant. How narrow or wide the ellipse is will be called its eccentricity. More on this later. use K on keyboard to Pause/Play
    4. 4. Another way to define the ellipse is this:An Ellipse is the set ofpoints in the plane thesum of whose distancesfrom two fixed points(the Foci), is a constant. How narrow or wide the ellipse is will be called its eccentricity. More on this later. use K on keyboard to Pause/Play
    5. 5. What follows is the derivation of the equation for an ellipse centered at the origin.
    6. 6. What follows is the derivation of the equation for an ellipse centered at the origin.You don’t need to write any of this down, but I want you to pay careful attention and understand the work.
    7. 7. Consider this ellipse centered at the Origin with foci onthe x-axis:and let the sum of F1P and F2 P be the constant 2awhich means ± a are the x-intercepts and a > c
    8. 8. Consider this ellipse centered at the Origin with foci onthe x-axis:and let the sum of F1P and F2 P be the constant 2awhich means ± a are the x-intercepts and a > c then 2 2 2 2 ( x + c) +y + ( x − c) + y = 2a
    9. 9. from the previous slide 2 2 2 2( x + c) +y + ( x − c) + y = 2a
    10. 10. from the previous slide 2 2 2 2( x + c) +y + ( x − c) + y = 2a 2 2 2 2( x − c) + y = 2a − ( x + c) +y
    11. 11. from the previous slide 2 2 2 2( x + c) +y + ( x − c) + y = 2a 2 2 2 2( x − c) + y = 2a − ( x + c) +ysquare both sides and expand
    12. 12. from the previous slide 2 2 2 2 ( x + c) +y + ( x − c) + y = 2a 2 2 2 2 ( x − c) + y = 2a − ( x + c) +y square both sides and expand 2 2 2 2 2 2 2 2 2x − 2cx + c + y = 4a − 4a ( x + c) + y + x + 2cx + c + y
    13. 13. from the previous slide 2 2 2 2 ( x + c) +y + ( x − c) + y = 2a 2 2 2 2 ( x − c) + y = 2a − ( x + c) +y square both sides and expand 2 2 2 2 2 2 2 2 2x − 2cx + c + y = 4a − 4a ( x + c) + y + x + 2cx + c + y
    14. 14. from the previous slide 2 2 2 2 ( x + c) +y + ( x − c) + y = 2a 2 2 2 2 ( x − c) + y = 2a − ( x + c) +y square both sides and expand 2 2 2 2 2 2 2 2 2x − 2cx + c + y = 4a − 4a ( x + c) + y + x + 2cx + c + y 2 2 2 4a ( x + c) + y = 4a + 4cx
    15. 15. from the previous slide 2 2 2 2 ( x + c) +y + ( x − c) + y = 2a 2 2 2 2 ( x − c) + y = 2a − ( x + c) +y square both sides and expand 2 2 2 2 2 2 2 2 2x − 2cx + c + y = 4a − 4a ( x + c) + y + x + 2cx + c + y 2 2 2 4a ( x + c) + y = 4a + 4cx 2 2 2 a ( x + c) + y = a + cx
    16. 16. from the previous slide 2 2 2a ( x + c) + y = a + cx
    17. 17. from the previous slide 2 2 2a ( x + c) + y = a + cx square both sides
    18. 18. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sidesa 2 (( x + c ) + y ) = a 2 2 4 2 2 + 2a cx + c x 2
    19. 19. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sides a 2 (( x + c ) + y ) = a 2 2 4 2 + 2a cx + c x 2 2 2 2 2 2 2 2 2 4 2 2 2a x + 2a cx + a c + a y = a + 2a cx + c x
    20. 20. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sides a 2 (( x + c ) + y ) = a 2 2 4 2 + 2a cx + c x 2 2 2 2 2 2 2 2 2 4 2 2 2a x + 2a cx + a c + a y = a + 2a cx + c x
    21. 21. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sides a 2 (( x + c ) + y ) = a 2 2 4 2 + 2a cx + c x 2 2 2 2 2 2 2 2 2 4 2 2 2a x + 2a cx + a c + a y = a + 2a cx + c x 2 2 2 2 2 2 4 2 2 a x +a c +a y =a +c x
    22. 22. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sides a 2 (( x + c ) + y ) = a 2 2 4 2 + 2a cx + c x 2 2 2 2 2 2 2 2 2 4 2 2 2 a x + 2a cx + a c + a y = a + 2a cx + c x 2 2 2 2 2 2 4 2 2 a x +a c +a y =a +c xsubtract each of these terms from both sides and group
    23. 23. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sides a 2 (( x + c ) + y ) = a 2 2 4 2 + 2a cx + c x 2 2 2 2 2 2 2 2 2 4 2 2 2 a x + 2a cx + a c + a y = a + 2a cx + c x 2 2 2 2 2 2 4 2 2 a x +a c +a y =a +c xsubtract each of these terms from both sides and group (a x 2 2 − c x )+ a y = a − a c 2 2 2 2 4 2 2
    24. 24. from the previous slide 2 2 2 a ( x + c) + y = a + cx square both sides a 2 (( x + c ) + y ) = a 2 2 4 2 + 2a cx + c x 2 2 2 2 2 2 2 2 2 4 2 2 2 a x + 2a cx + a c + a y = a + 2a cx + c x 2 2 2 2 2 2 4 2 2 a x +a c +a y =a +c xsubtract each of these terms from both sides and group (a x 2 2 − c x )+ a y = a − a c 2 2 2 2 4 2 2 x (a 2 2 − c ) + a y = a (a − c 2 2 2 2 2 2 )
    25. 25. from the previous slidex (a − c ) + a y = a (a − c 2 2 2 2 2 2 2 2 )
    26. 26. from the previous slide x (a − c ) + a y = a (a − c 2 2 2 2 2 2 2 2 )recall that a > c , so a − c > 0 and 2 2 2 (we can divide by a a − c2 2 )
    27. 27. from the previous slide x (a − c ) + a y = a (a − c 2 2 2 2 2 2 2 2 )recall that a > c , so a − c > 0 and 2 2 2 (we can divide by a a − c2 2 ) 2 2 x y 2 + 2 2 =1 a a −c
    28. 28. from the previous slide x (a − c ) + a y = a (a − c 2 2 2 2 2 2 2 2 )recall that a > c , so a − c > 0 and 2 2we can divide by a a − c 2 2 (2 ) 2 2 x y 2 + 2 2 =1 a a −cthen we let b = a − c 2 2 2 ( and b < a )to get the familiar:
    29. 29. from the previous slide x (a − c ) + a y = a (a − c 2 2 2 2 2 2 2 2 )recall that a > c , so a − c > 0 and 2 2we can divide by a a − c 2 2 2 ( ) 2 2 x y 2 + 2 2 =1 a a −cthen we let b = a − c 2 2 2 ( and b < a )to get the familiar: 2 2 x y 2 + 2 =1 a b
    30. 30. 2 2 x y 2 + 2 =1 a bmajor axis has length 2aminor axis has length 2b
    31. 31. 2 2 x y 2 + 2 =1 b amajor axis has length 2aminor axis has length 2b
    32. 32. To sketch the graph of an ellipse, find the lengths ofthe major and minor axes ... and sketch away! Pleaseinclude the foci.
    33. 33. Example: Sketch the graph of 4x 2 + 25y 2 = 100
    34. 34. Example: Sketch the graph of 4x 2 + 25y 2 = 100 divide by the constant to put it into standard form
    35. 35. Example: Sketch the graph of 4x 2 + 25y 2 = 100 divide by the constant to put it into standard form 2 2 x y + =1 25 4
    36. 36. Example: Sketch the graph of 4x 2 + 25y 2 = 100 divide by the constant to put it into standard form 2 2 x y + =1 25 4 2 a = 25 a = ±5
    37. 37. Example: Sketch the graph of 4x 2 + 25y 2 = 100 divide by the constant to put it into standard form 2 2 x y + =1 25 4 2 2 a = 25 b =4 a = ±5 b = ±2
    38. 38. Example: Sketch the graph of 4x 2 + 25y 2 = 100 divide by the constant to put it into standard form 2 2 x y + =1 25 4 2 2 2 2 2 a = 25 b =4 c = a −b 2 a = ±5 b = ±2 c = 25 − 4 c = ± 21
    39. 39. Example: Sketch the graph of 4x 2 + 25y 2 = 100 divide by the constant to put it into standard form 2 2 x y + =1 25 4 2 2 2 2 2 a = 25 b =4 c = a −b 2 a = ±5 b = ±2 c = 25 − 4 c = ± 21
    40. 40. HW #3“As a rule of thumb, involve everyone in everything.” Tom Peters

    ×